STUDI KASUS KEBERMINATAN SISWA SMK UNTUK MELANJUTKAN STUDI KE UNIVERSITAS BHINNEKA PGRI PROGRAM STUDI PVTO - Mohammad Muthohirul Azis; Anggara Sukma Ardiyanta (Journal of Automotive Vocational Education (JAVED), 2024)
This research aims to find out (1) why students' interest in continuing to college is lacking, (2) the factors behind the lack of interest of vocational students to continue to college, (3) find ways to make vocational students want to continue to college. This research is a descriptive qualitative research with a case study approach. There were 59 informants in this study. The data collection technique used purposive sampling and snowball sampling. The data collection process used in-depth interviews, observation, and documentation. The data analysis technique uses Milles and Huberman's interactive analysis model with data collection, data reduction, data presentation, and conclusion drawing. The validity of the data used is trustworthiness, transferability, dependability, and certainty. The results showed that (1) there are still vocational students who are interested in continuing to college so that their interest is there, not less. (2) the factors behind the lack of interest of vocational students to continue to college include (a) internal factors in the form of willingness and academic success. (b) external factors such as cost, family environment, and school environment. (3) The ways to make high school students interested in continuing to college are (a) Conducting separate socialization of automotive technology vocational education study programs. (b) Cooperate with the school. (c) Creating a mentored class. (d) Creating interesting activities. (e) Provide scholarships. (f) Doing social media branding.Keywords: Interest,Vocational Students, Continuing Their Studies